Allergic Reaction to a Red Plastic Allergy Alert Patient Identification Bracelet: Implications for Surgical Patient Safety. Issue 7 (July 2013) - Colbert, Serryth; Williams, John V; Mackenzie, Neil; Brennan, Peter A
We present a case of allergy to a hospital thermally-printed red plastic allergy alert bracelet in a 48 year old lady admitted to the day surgery unit. Two hours postoperatively, an intensely itchy area of erythema and oedema was seen extending from her left wrist distally to the fingers. The bracelet was removed and the rash resolved overnight without further complication. A diagnosis of contact dermatitis was made, secondary to exposure to an agent within the bracelet. We discuss the safety implications for surgical patients unable to wear an identification bracelet and the steps that may be taken to minimise the risk of harm from misidentification. We believe this to be the first documented case of an allergy to a patient identification bracelet in the medical literature.